1984
DOI: 10.1007/bf01254760
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a symptom in depressive disorders and its relationship to platelet monoamine oxidase activity

Abstract: 144 depressed in-patients were rated by means of the Comprehensive Psychopathological Rating Scale (CPRS) and platelet monoamine oxidase (MAO) was determined. 49 per cent of the patients were found to have pain as a symptom, and 21 per cent were found to have more severe pain. The patients with more severe pain were found to have lower platelet MAO activity than the patients without pain or with slight pain. As platelet MAO activity may reflect the turn-over in the serotinergic systems in CNS it is hypothesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…variations in severity of these emotional states, may prove to be equally important. On the other hand, constitutional vulnerability factors may contribute to this putative screening mechanism of emotional precipitation of attacks; it has been suggested that there is a close relationship between pain systems and emotional regulation systems through defective endorphinic or serotoninergic and adrenergic systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…variations in severity of these emotional states, may prove to be equally important. On the other hand, constitutional vulnerability factors may contribute to this putative screening mechanism of emotional precipitation of attacks; it has been suggested that there is a close relationship between pain systems and emotional regulation systems through defective endorphinic or serotoninergic and adrenergic systems (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The secondary symptoms are: (i) loss of appetite, (ii) insomnia [increased amount and decreased latency of rapid eye movement (REM) sleep, as deter-mined by EEG measurements], (iii) motor retardation or agitation, (iv) feelings of worthlessness or guilt, (v) continues fatigue, (vi) cognitive difficulties, and (vii) suicidal thoughts [57]. The following physiological and biochemical characteristics are often observed in depressed patients: (i) chronic pain [50% of the depressed patients suffer from chronic pain [58,59], (ii) high levels of plasma cortisol [60,61], (iii) resistance in the dexamethasone suppression test [62], (iv) supersensitivity to cholinergic agonists [63][64][65][66], and (v) first degree relatives that also suffer from depressive disorders, i.e, a genetic component [67].…”
Section: Depressionmentioning
confidence: 99%
“…21 Patients with depression and severe pain may also have lower levels of monoamine oxidase activity than depressed patients without pain. 10 Such mechanisms have also been proposed to account for the effects of some antidepressants on both affective and painful symptoms. [22][23][24] It has also been suggested that low levels of serotonin and noradrenaline, which occur in depression, may affect pain modulating pathways.…”
Section: Healthcare Resource Usementioning
confidence: 99%